2007
DOI: 10.1007/s12098-007-0199-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-laboratory profile of pediatric HIV in Karnataka

Abstract: Vertical transmission was the major route of HIV infection. Persistent fever, cough, loss of appetite and loss of weight were common presenting clinical features. Tuberculosis was the commonest opportunistic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
25
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 8 publications
13
25
5
Order By: Relevance
“…(Table 3) This study is comparable with Diack et al , who found vertical transmission in 99% cases, Pol R et al, reported it in 94.37% cases. 14,18 But in our study vertical transmission was seen in 98.15% cases which is slightly higher than that reported by Merchant RH et al, as 86.6%. 19 Verghese VP et al, found vertical transmission in 87% cases.…”
Section: Fromcontrasting
confidence: 63%
See 1 more Smart Citation
“…(Table 3) This study is comparable with Diack et al , who found vertical transmission in 99% cases, Pol R et al, reported it in 94.37% cases. 14,18 But in our study vertical transmission was seen in 98.15% cases which is slightly higher than that reported by Merchant RH et al, as 86.6%. 19 Verghese VP et al, found vertical transmission in 87% cases.…”
Section: Fromcontrasting
confidence: 63%
“…This ratio is comparable to study by Madhivanan P et al, who found it to be 2.05:1, Shahab T et al, who found it to be 2.3:1 and Pol R et al, in Karnataka found the ratio as 1.73:1. 14,16,17 This male preponderance might be due to the social structure of our society especially in rural areas where males are given better care than females, from where this study is done.…”
Section: Frommentioning
confidence: 99%
“…These results supported the findings obtained by Pol et al [15] in HIV-infected children in the state of Karnataka who reported tuberculosis as the most common opportunistic infection. While, Shahapur and Bairy [16] reported oral candidiasis and recurrent respiratory tract infection as the commonest opportunistic infections in children infected with HIV in Southern India.…”
Section: Introductionsupporting
confidence: 92%
“…Pol et al observed 56.3% seropositive children who had weight loss >10%. 16 Difference in weight loss can be explained as study by Pol et al conducted in children >18 months of age. 16 Shah et al observed weight loss >10% in 50% of seropositive cases.…”
Section: Discussionmentioning
confidence: 99%
“…16 Difference in weight loss can be explained as study by Pol et al conducted in children >18 months of age. 16 Shah et al observed weight loss >10% in 50% of seropositive cases. 17 This incidence of more weight loss as compared to our study can be explained as Shah et al conducted their study in children >1 month of age.…”
Section: Discussionmentioning
confidence: 99%